2001
DOI: 10.1074/jbc.m008348200
|View full text |Cite
|
Sign up to set email alerts
|

Stable Activation of Single Ca2+ Release-activated Ca2+ Channels in Divalent Cation-free Solutions

Abstract: The regulation of store-operated, calcium-selective channels in the plasma membrane of rat basophilic leukemia cells (RBL-2H3 m1), an immortalized mucosal mast cell line, was studied at the single-channel level with the patch clamp technique by removing divalent cations from both sides of the membrane. The activity of the single channels in excised patches could be modulated by Ca 2؉ , Mg 2؉ , and pH. The maximal activation of these channels by divalent cation-free conditions occurred independently of depletio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
106
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(121 citation statements)
references
References 26 publications
13
106
2
Order By: Relevance
“…These observations provide strong evidence against a requisite role for SNARE-mediated membrane fusion in the coupling of SOC activation to calcium store depletion. This conclusion is consistent with the notion that the SOC channels, and the machinery necessary to activate them, exist in the plasma membrane prior to activation, as predicted by the observation of single store-operated channel openings in excised membrane patches (35).…”
Section: Discussionsupporting
confidence: 78%
“…These observations provide strong evidence against a requisite role for SNARE-mediated membrane fusion in the coupling of SOC activation to calcium store depletion. This conclusion is consistent with the notion that the SOC channels, and the machinery necessary to activate them, exist in the plasma membrane prior to activation, as predicted by the observation of single store-operated channel openings in excised membrane patches (35).…”
Section: Discussionsupporting
confidence: 78%
“…The inhibitory actions of 2-APB differed markedly, both quantitatively and qualitatively, among the three Orai species, consistent with but not proving a direct effect on the channels themselves. Earlier findings from a number of laboratories suggest an extracellular site of action of 2-APB on I CRAC (24,26,27), which is further consistent with a direct action on the channel. Both Orai1 and -3 could also be activated by 2-APB, and Orai3 channels additionally showed altered ion selectivity when activated by 2-APB.…”
Section: Discussionsupporting
confidence: 60%
“…It has been shown in rat hippocampal astrocytes that Ca 2ϩ oscillations were attributable to phospholipase C-mediated Ca 2ϩ release from intracellular stores (Zur Nieden and Deitmer, 2006). 2-APB effectively inhibits SOCE channels in many cell types (Bakowski et al, 2001;Braun et al, 2001;Broad et al, 2001;Gregory et al, 2001;Kukkonen et al, 2001;Prakriya and Lewis, 2001) but can also be a membranepermeable inhibitor of IP 3 receptors (Wu et al, 2000). We observed that the number of spontaneously active astrocytes as well as the frequency of oscillations were reduced by blocking SOCE channels and by inhibiting iPLA 2 activity.…”
Section: Camentioning
confidence: 57%